An investigation of international hotel productivity considering quasifixed inputs and negative outputs. (22nd November 2019) - Fang, David; Hsueh, Ming‐Ching; Chiu, Ching‐Ren
Abstract : This paper explores the productivity of international hotels by considering the number of guest rooms and the area of the catering department as quasifixed inputs, because neither can be easily changed over a short period. We introduce a range‐adjusted measure model to incorporate both quasifixed inputs and negative outputs and propose a nonradial Malmquist productivity index to estimate dynamic productivity. The results show that chain‐operated hotels were unable to generate operational synergy to enhance their competitiveness, but their productivity outperformed that of independently operated hotels in cross‐period aspect. Finally, we provide improvement suggestions for managers.